English Alveolar /t/ And Approximant /ɹ/ Convergence Phenomenon in Indonesians’ Interaction: Reflection of Social Dynamics - Kania, Annisa Nurhijatul; Roselani, Ni Gusti Ayu (Universitas Gadjah Mada, 2025)
This study investigates the phenomenon of sound convergence in Indonesian-English bilingual interactions, focusing on a podcast setting. This study investigates three key aspects; the convergence of two English sounds: alveolar /t/ to Indonesian dental /t̪/ and approximant /ɹ/ to Indonesian trilled /r/ using Phonetic and Phonology approach; the reciprocal nature of the convergence; the social factors motivating this linguistic behavior using Communication Accommodation Theory (CAT) approach.. The data collected from six podcast episodes reveal that reciprocity played a significant role in the frequency of convergence, with higher levels of mutual adjustment leading to increased overall convergence. Additionally, the speakers' educational backgrounds, particularly those from prestigious universities, influence the emergence of sound convergence. This research contributes to our understanding of sound convergence in multilingual contexts, shedding light on the complex relationship between language, identity, and social factors. The findings have implications for language education, cross-cultural communication practices, and our broader understanding of how linguistic choices reflect social structures in bilingual settings.